A composite scale inhibitor and preparation method thereof
By using a composite scale inhibitor in industrial circulation cooling water, combined with the combination of maleic anhydride, sodium para-styrene sulfonate, taurocholic acid and N-phenyl anthranilic acid, the complexity of the scale problem in the prior art and the environmental pollution risk of phosphorus scale inhibitors are solved, and an efficient and environmentally friendly scale inhibitor effect is achieved.
Patent Information
- Application Number
- CN202411930359.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the scaling problem in industrial circulation cooling water is difficult to effectively solve under complex water quality conditions, and the phosphorus-based scale inhibitor has a risk of environmental pollution.
The preparation method of composite scale inhibitors is adopted to form a scale inhibitor with good hydrophilicity and dispersion properties through the combination of maleic anhydride, sodium para-styrene sulfonate, taurocholic acid and N-phenyl anthranilic acid. The scale inhibitors are enhanced by using the esterification reaction, chelation and coordination of these components.
The scale inhibitor has achieved stable dispersion and anti-precipitation effects in complex water environments, and is phosphorus-free and environmentally friendly, improving scale inhibition performance and environmental friendliness.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a composite scale inhibitor and a preparation method thereof. Background Art
[0002] Industrial circulating cooling water, which consumes the most water resources, contains a large amount of scaling ions, salts, suspended solids and impurities, which will precipitate and adhere to the solid surface, thus causing scaling and posing safety hazards. Therefore, the scaling problem in industrial circulating cooling water must be given high attention.
[0003] With the progress of industry, the preparation and performance research of efficient and low-cost scale inhibitors have received more and more attention. At present, most scale inhibitors used are phosphorus-containing scale inhibitors. Although phosphorus-based scale inhibitors have solved the scaling problem to a certain extent, with the discharge of cooling water, the presence of phosphorus elements is likely to cause secondary pollution to the environment, which limits their use.
[0004] Nowadays, the ion composition of many sewages is complex and high in content, while most scale inhibitors in the existing technology are single-component scale inhibitors, which have insufficient performance under complex water conditions and are difficult to stably exert their dispersion and anti-sedimentation effects in different water environments.
[0005] Therefore, it is necessary to provide a composite scale inhibitor and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0006] In view of this, the present invention provides a composite scale inhibitor and a preparation method thereof, which can achieve the purpose of strong dispersibility of the scale inhibitor, good anti-precipitation effect and phosphorus-free and environmentally friendly.
[0007] The specific scheme of the present invention is as follows: a method for preparing a composite antiscalant comprises the following steps:
[0008] Step S1, preparation of a precursor mixture, adding maleic anhydride and sodium p-styrene sulfonate into a reaction kettle, adding deionized water, stirring evenly, adding an initiator, heating and stirring, then adding taurocholic acid, stirring, and cooling to obtain a precursor mixed solution;
[0009] Step S2, preparation of a composite scale inhibitor, adding N-phenylanthranilic acid to the precursor mixed solution, stirring, ultrasonic treatment and then spray drying to obtain a composite scale inhibitor.
[0010] Taurocholic acid is formed by the combination of taurine (with sulfonic acid group) and ursodeoxycholic acid (with hydroxyl group and carboxyl group). It has good hydrophilicity. The hydroxyl group in taurocholic acid can undergo esterification reaction with the carboxyl group of maleic anhydride to form a stable composite structure, which can enhance the hydrophilicity and dispersibility of the scale inhibitor.
[0011] The carboxyl and hydroxyl groups in taurocholic acid can form stable chelates with free ions such as calcium and magnesium ions through coordination. The chelation reduces the concentration of free ions such as calcium and magnesium ions in the solution, and reduces the chance of these ions forming insoluble salt scale with carbonate, sulfate, etc. Hydroxyl and carboxyl groups can coordinate with the crystal surface, cover the active sites of the crystal, inhibit the deposition of new ions, interfere with the surface growth of salt scale crystals, and further improve the scale inhibition performance of the scale inhibitor.
[0012] The sulfonic acid group in sodium p-styrene sulfonate has strong hydrophilicity in water, which further improves the dispersibility and water solubility of the scale inhibitor, allowing the scale inhibitor to be evenly dispersed in water. Maleic anhydride and sodium p-styrene sulfonate can be polymerized, and then the esterification reaction of maleic anhydride and taurocholic acid can form a stable composite structure, which not only enables the scale inhibitor to stably exert its scale inhibition performance in a complex water environment, but also provides more active sites for scale inhibition, enhancing the anti-precipitation effect of the scale inhibitor.
[0013] N-phenyl anthranilic acid contains carboxyl and amino groups. The carboxyl group can provide electrons and form coordination bonds with metal ions such as calcium ions and magnesium ions through coordination to form stable chelates. The amino group has lone pairs of electrons, which can further enhance the coordination ability of metal ions, form bidentate coordination chelate rings, improve the stability of chelates, and improve the scale inhibition performance of scale inhibitors. Carboxyl and amino groups can also be adsorbed on the surface of scaling crystals to prevent ions from depositing on the surface of scaling crystals, forming a synergistic effect with taurocholic acid, and further enhancing the anti-deposition effect of scale inhibitors. In addition, the benzene ring of N-phenyl anthranilic acid provides a certain hydrophobicity, which can destroy the regular arrangement of scaling crystals, resulting in the formation of crystal defects, making scaling crystals easier to disperse in the solution, and enhancing the scale inhibition effect of scale inhibitors.
[0014] Preferably, in step S1, the stirring speed is 400-500 rpm, the time is 50-70 minutes; the heating stirring speed is 200-300 rpm, the time is 1.5-2.5 hours, and the temperature is 50-60°C; the stirring speed is 400-500 rm, the time is 60-70 minutes, and the temperature is 60-70°C.
[0015] Preferably, in step S1, the initiator includes one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0016] Preferably, in step S2, the stirring speed is 400-500 rpm, and the time is 2-2.5 hours; and the time of ultrasonic treatment is 20-30 minutes.
[0017] Preferably, in step S2, functionalized UIO-66 is added before adding N-phenylanthranilic acid, and the mixture is stirred at 300-400 rpm for 3-4 hours to be uniformly mixed.
[0018] Preferably, the functionalized UIO-66 (metal organic framework) is prepared by the following steps: adding the hydrated UIO-66 to a sodium p-styrene sulfonate solution, heating and stirring, filtering, washing, and drying to obtain the functionalized UIO-66.
[0019] The hydration process can stabilize the structure of UIO-66. Especially when it needs to be used in an aqueous environment, the UIO-66 material can be adapted to the moisture environment in advance, so that the UIO-66 material can be fully dispersed in water, which can increase the surface area of the material in contact with the solvent, thereby improving the activity of the material and reducing structural changes or performance degradation caused by moisture absorption.
[0020] The sulfonic acid group in sodium p-styrene sulfonate can form a stable chemical bond with the organic ligand in UIO-66, fix the sulfonic acid group on the surface of UIO-66, and achieve surface modification of UIO-66. Sulfonic acid group is a hydrophilic group that can enhance the hydrophilicity of the surface of UIO-66 and reduce the interaction between UIO-66, thereby preventing its agglomeration, improving its dispersion performance, maintaining its high specific surface area and porous structure, and facilitating its application in aqueous phase systems. The modified UIO-66 has higher surface activity and can better adsorb target molecules to participate in the reaction, so that the scale inhibition effect of taurocholic acid, maleic anhydride and sodium p-styrene sulfonate in the scale inhibitor can be better exerted, and the scale inhibition performance of the scale inhibitor is greatly improved.
[0021] Preferably, the hydrated UIO-66 is prepared by the following steps: adding UIO-66 to deionized water, stirring at a speed of 400-500 rpm for 1-2 hours to ensure that the surface is fully hydrated, and obtaining the hydrated UIO-66.
[0022] Preferably, the heating and stirring speed is 300-500 rpm, the time is 60-90 minutes, and the temperature is 45-55° C.; the drying temperature is 55-65° C., and the time is 10-12 hours.
[0023] To achieve the above object, the present invention also provides a composite scale inhibitor prepared by the above-mentioned method for preparing a composite scale inhibitor, comprising the following components in parts by weight:
[0024] 5-10 parts of maleic anhydride, 5-10 parts of sodium p-styrene sulfonate, 0.5-1 parts of initiator, 3-5 parts of taurocholic acid and 2-3 parts of N-phenylanthranilic acid.
[0025] Preferably, the scale inhibitor further comprises the following components in parts by weight:
[0026] Functionalized UIO-66 2-3 copies;
[0027] The raw materials of the functionalized UIO-66 include 5-6 parts of UIO-66, 100-120 parts of deionized water and 1-2 parts of sodium p-styrene sulfonate.
[0028] The above technical solution of the present invention includes at least the following beneficial effects:
[0029] (1) The present invention uses taurocholic acid. Taurocholic acid itself contains sulfonic acid group, hydroxyl group and carboxyl group, has good hydrophilicity, and can undergo esterification reaction with maleic anhydride to form a stable composite structure, thereby enhancing the hydrophilicity and dispersibility of the scale inhibitor; at the same time, its carboxyl group and hydroxyl group can form chelates with metal ions through coordination, inhibit metal ion deposition, interfere with the surface growth of salt scale crystals, and achieve enhanced scale inhibition performance.
[0030] (2) Sodium p-styrene sulfonate has a sulfonic acid group, which helps to further improve the hydrophilicity and dispersibility of the scale inhibitor. It combines with maleic anhydride to form a stable composite structure, which enhances the stability of the scale inhibitor, enabling the scale inhibitor to play its anti-precipitation role in complex water environments and achieve the goal of phosphorus-free and environmentally friendly.
[0031] (3) N-phenylanthranilic acid contains carboxyl and amino groups. The carboxyl group can provide electrons to form stable chelates with calcium and magnesium ions. The amino group has lone pairs of electrons, which further enhances the coordination ability of the scale inhibitor to metal ions, forms a bidentate coordination chelate ring, improves the stability of the chelate, and achieves long-term effect of the scale inhibitor. In addition, the benzene ring of N-phenylanthranilic acid provides a certain degree of hydrophobicity, which can destroy the regular arrangement of scaling crystals, leading to the formation of scaling crystal defects, making scaling crystals easier to disperse in the solution, reducing scaling, and enhancing the scale inhibition effect of the scale inhibitor. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0033] Example 1
[0034] Take 5 parts of UIO-66 and add them to 100 parts of deionized water. Stir at 450 rpm for 1 hour to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 1.5 parts of sodium p-styrene sulfonate solution, heat to 50 °C, stir at 400 rpm for 70 minutes, filter, wash, and dry in an oven (60 °C) for 12 hours to obtain functionalized UIO-66.
[0035] Add 7 parts of maleic anhydride and 8 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 450 rpm for 60 minutes, add 1 part of ammonium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 55°C, stir at 300 rpm for 2 hours to form a preliminary polymer, then slowly add 5 parts of taurocholic acid, raise the temperature to 65°C, stir at 400 rpm for 70 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0036] Add 2 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 300 rpm for 4 hours to ensure uniform mixing, then add 3 parts of N-phenyl anthranilic acid, stir at 450 rpm, keep stirring for 2 hours, treat the mixed solution with ultrasound for 20 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0037] Example 2
[0038] Take 5 parts of UIO-66 and add them to 110 parts of deionized water. Stir at 400 rpm for 2 hours to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 2 parts of sodium p-styrene sulfonate solution, heat to 55 °C, stir at 350 rpm for 60 minutes, filter, wash, and dry in an oven (65 °C) for 11 hours to obtain functionalized UIO-66.
[0039] Add 8 parts of maleic anhydride and 8 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 450 rpm for 70 minutes, add 0.5 parts of sodium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 50°C, stir at 200 rpm for 2.5 hours to form a preliminary polymer, then slowly add 4 parts of taurocholic acid, raise the temperature to 70°C, stir at 500 rpm for 65 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0040] Add 2.5 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 400 rpm for 3 hours to ensure uniform mixing, then add 2.5 parts of N-phenyl anthranilic acid, stir at 400 rpm for 2.5 hours, treat the mixed solution with ultrasound for 25 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0041] Example 3
[0042] Take 6 parts of UIO-66 and add them to 100 parts of deionized water. Stir at 400 rpm for 1.5 hours to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 2 parts of sodium p-styrene sulfonate solution, heat to 50°C, stir at 300 rpm for 90 minutes, filter, wash, and dry in an oven (55°C) for 12 hours to obtain functionalized UIO-66.
[0043] Add 6 parts of maleic anhydride and 10 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 400 rpm for 70 minutes, add 0.5 parts of ammonium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 60°C, stir at 250 rpm for 2.5 hours to form a preliminary polymer, then slowly add 5 parts of taurocholic acid, raise the temperature to 60°C, stir at 500 rpm for 60 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0044] Add 3 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 350 rpm for 3.5 hours to ensure uniform mixing, then add 3 parts of N-phenyl anthranilic acid, stir at 500 rpm, keep stirring for 2 hours, treat the mixed solution with ultrasound for 25 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0045] Example 4
[0046] Take 5.5 parts of UIO-66 and add them to 120 parts of deionized water. Stir at 500 rpm for 1 hour to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 1.5 parts of sodium p-styrene sulfonate solution, heat to 45°C, stir at 500 rpm for 65 minutes, filter, wash, and dry in an oven (55°C) for 10 hours to obtain functionalized UIO-66.
[0047] Add 5 parts of maleic anhydride and 10 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 500 rpm for 60 minutes, add 0.7 parts of sodium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 50°C, stir at 250 rpm for 1.5 hours to form a preliminary polymer, then slowly add 3 parts of taurocholic acid, raise the temperature to 65°C, stir at 450 rpm for 65 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0048] Add 3 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 350 rpm for 4 hours to ensure uniform mixing, then add 2 parts of N-phenyl anthranilic acid, stir at 400 rpm, keep stirring for 2.5 hours, treat the mixed solution with ultrasound for 30 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0049] Example 5
[0050] Take 5 parts of UIO-66 and add them to 120 parts of deionized water. Stir at 500 rpm for 1.5 hours to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 2 parts of sodium p-styrene sulfonate solution, heat to 45 °C, stir at 400 rpm for 80 minutes, filter, wash, and dry in an oven (57 °C) for 10 hours to obtain functionalized UIO-66.
[0051] Add 10 parts of maleic anhydride and 5 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 500 rpm for 50 minutes, add 0.9 parts of potassium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 60°C, stir at 200 rpm for 2 hours to form a preliminary polymer, then slowly add 5 parts of taurocholic acid, raise the temperature to 70°C, stir at 400 rpm for 65 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0052] Add 3 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 300 rpm for 4 hours to ensure uniform mixing, then add 3 parts of N-phenyl anthranilic acid, stir at 450 rpm, keep stirring for 2 hours, treat the mixed solution with ultrasound for 30 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0053] Example 6
[0054] Take 5 parts of UIO-66 and add them to 100 parts of deionized water, stir at 450 rpm for 1.5 hours to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 1 part of sodium p-styrene sulfonate solution, heat to 55°C, stir at 450 rpm for 75 minutes, filter, wash, and dry in an oven (63°C) for 12 hours to obtain functionalized UIO-66.
[0055] Add 9 parts of maleic anhydride and 6 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 400 rpm for 65 minutes, add 1 part of ammonium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 50°C, stir at 270 rpm for 1.5 hours to form a preliminary polymer, then slowly add 4 parts of taurocholic acid, raise the temperature to 70°C, stir at 450 rpm for 60 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0056] Add 2.5 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 400 rpm for 3.5 hours to ensure uniform mixing, then add 3 parts of N-phenyl anthranilic acid, stir at 450 rpm, keep stirring for 2.5 hours, treat the mixed solution with ultrasound for 20 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0057] Example 7
[0058] Take 5.5 parts of UIO-66 and add them to 100 parts of deionized water. Stir at 450 rpm for 2 hours to ensure that its surface is fully hydrated. Add the hydrated UIO-66 to 1.5 parts of sodium p-styrene sulfonate solution, heat to 50°C, stir at 300 rpm for 80 minutes, filter, wash, and dry in an oven (65°C) for 11 hours to obtain functionalized UIO-66.
[0059] Add 7 parts of maleic anhydride and 9 parts of sodium p-styrene sulfonate to the reactor, add 500 parts of deionized water, stir at 500 rpm for 55 minutes, add 0.6 parts of sodium persulfate as an initiator after stirring evenly, heat, control the reaction temperature to a constant 60°C, stir at 230 rpm for 2 hours to form a preliminary polymer, then slowly add 3 parts of taurocholic acid, raise the temperature to 65°C, stir at 470 rpm for 60 minutes, and then cool to room temperature to obtain a precursor mixed solution.
[0060] Add 3 parts of dry functionalized UIO-66 to the precursor mixed solution, stir at 330 rpm for 3.5 hours to ensure uniform mixing, then add 2.5 parts of N-phenyl anthranilic acid, stir at 400 rpm, keep stirring for 2.5 hours, treat the mixed solution with ultrasound for 20 minutes to ensure uniform dispersion, and spray dry to obtain a composite scale inhibitor.
[0061] Example 8
[0062] The difference between Example 8 and Example 7 is that functionalized UIO-66 is not used, and the other compositions and preparation methods are the same as those of Example 7, and a composite scale inhibitor is prepared.
[0063] The present invention also carries out comparative examples and related tests.
[0064] Comparative Example 1
[0065] The difference between Comparative Example 1 and Example 1 is that taurocholic acid is not used, and other compositions and preparation methods are the same as those of Example 1, and a composite scale inhibitor is prepared.
[0066] Comparative Example 2
[0067] The difference between Comparative Example 2 and Example 1 is that N-phenylanthranilic acid is not used, and the other compositions and preparation methods are the same as those of Example 1, and a composite scale inhibitor is prepared.
[0068] Comparative Example 3
[0069] Commercially available scale inhibitor, WL-602 purchased from Chongqing Wolan Water Treatment Equipment Co., Ltd.
[0070] Performance testing
[0071] The scale inhibition effect of the scale inhibitors prepared in Examples 1-8 and Comparative Examples 1-3 was tested according to the following reference standards.
[0072] Referring to the calcium carbonate precipitation method standard GB / T16632-2019, a calcium carbonate scale inhibition test was carried out. The test temperature was 80°C and the test time was 10 hours. The scale inhibition rate (%) was the specific test result, as shown in Table 1.
[0073] Table 1
[0074]
[0075] Referring to the calcium phosphate precipitation method standard GB / T22626-2008, a calcium phosphate scale inhibition test was carried out. The test temperature was 80°C and the test time was 10 hours. The scale inhibition rate (%) was the specific test result, as shown in Table 2.
[0076] Table 2
[0077]
[0078] According to the data in Table 1 and Table 2, the scale inhibition efficiency of the scale inhibitor prepared in Comparative Example 1 on calcium carbonate and calcium phosphate is much lower than that of the scale inhibitor prepared in Examples 1-8. It can be seen that taurocholic acid has a significant improvement on the performance of the scale inhibitor, indicating that the addition of taurocholic acid increases the content of sulfonic acid and carboxyl groups in the scale inhibitor, thereby enhancing the scale inhibition effect; the scale inhibition efficiency of the scale inhibitor prepared in Comparative Example 2 is somewhat lower than that of Examples 1-8, indicating that N-phenylanthranilic acid can enhance the coordination effect of the scale inhibitor on metal ions and improve its scale inhibition efficiency; Comparative Example 3 uses a commercially available scale inhibitor, indicating that the scale inhibition performance of the scale inhibitor prepared in Examples 1-8 is higher than that of commercially available products; the scale inhibition efficiency of the scale inhibitor prepared in Example 8 is lower than that of the scale inhibitor prepared in Example 7, indicating that functionalized UIO-66 is helpful to improve the scale inhibition performance of the scale inhibitor.
[0079] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a composite scale inhibitor, characterized in that: The following steps are involved: Step S1, preparation of a precursor mixture, adding 5-10 parts by weight of maleic anhydride and 5-10 parts by weight of sodium p-styrene sulfonate to a reaction kettle, adding deionized water, stirring evenly, adding 0.5-1 parts by weight of an initiator, heating and stirring, then adding 3-5 parts by weight of taurocholic acid, stirring, and cooling to obtain a precursor mixed solution; Step S2, preparation of a composite scale inhibitor, adding 2-3 parts by weight of functionalized UIO-66 to the precursor mixed solution, mixing evenly, then adding 2-3 parts by weight of N-phenylanthranilic acid, stirring, ultrasonically treating, and spray drying to obtain a composite scale inhibitor; The raw materials for preparing the functionalized UIO-66 include 5-6 parts by mass of UIO-66, 100-120 parts by mass of deionized water and 1-2 parts by mass of sodium p-styrene sulfonate; the functionalized UIO-66 is prepared by the following steps: adding the hydrated UIO-66 to a sodium p-styrene sulfonate solution, heating and stirring, filtering, washing and drying to obtain the functionalized UIO-66.
2. The method for preparing a composite scale inhibitor according to claim 1, characterized in that: In the step S1, the stirring speed is 400-500 rpm, the time is 50-70 minutes; the heating stirring speed is 200-300 rpm, the time is 1.5-2.5 hours, and the temperature is 50-60°C; after adding taurocholic acid, the stirring speed is 400-500 rm, the time is 60-70 minutes, and the temperature is 60-70°C.
3. The method for preparing a composite scale inhibitor according to claim 1, characterized in that: In the step S1, the initiator includes one of ammonium persulfate, sodium persulfate and potassium persulfate.
4. The method for preparing a composite antiscalant according to claim 1, characterized in that: In the step S2, the stirring speed is 400-500 rpm for 2-2.5 hours; and the ultrasonic treatment time is 20-30 minutes.
5. The method for preparing a composite scale inhibitor according to claim 1, characterized in that: In the step S2, functionalized UIO-66 is added and stirred at a speed of 300-400 rpm for 3-4 hours to mix evenly.
6. The method for preparing a composite antiscalant according to claim 1, characterized in that: The hydrated UIO-66 is prepared by the following steps: adding UIO-66 to deionized water, stirring at a speed of 400-500 rpm for 1-2 hours to ensure that the surface is fully hydrated, and obtaining the hydrated UIO-66.
7. The method for preparing a composite antiscalant according to claim 1, characterized in that: In the step of preparing the functionalized UIO-66, the heating and stirring speed is 300-500 rpm, the time is 60-90 minutes, and the temperature is 45-55° C.; the drying temperature is 55-65° C., and the time is 10-12 hours.
8. A composite scale inhibitor, characterized in that: The composite scale inhibitor is prepared by the preparation method of any one of claims 1 to 7.
Citation Information
Patent Citations
Scale-inhibiting cocrystals for treatment of a subterranean formation
US20160130496A1